HUKUM ISLAM VS PSIKOLOGI : Pengenalan Ancaman Fenomena LGBT Pada Remaja di MTs. Annida Bina Insani Rancabungur - Warsih, Warsih; Pradana, Fahri; Silaturahmi, Muhammad; Wicaksono, Bimo Ario; Karimah, Syahadah Albaqiyatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The LGBT phenomenon, which is considered deviant behavior, is currently prevalent in society, causing concerns from various parties. Additionally, parents of students are also worried that the behavior of LGBT individuals may have negative consequences, similar to other contagious diseases, through the interaction of children, whether within the school environment or in social circles. The purpose of this community service activity is a preventive measure against deviant behavior threats like LGBT and to examine it from the perspectives of Islamic Law and Psychology. The method of implementing this activity is through sharing sessions. The outcome of this activity is an increased understanding and knowledge regarding the impact and threats of the dangers in the LGBT phenomenon in society from both Islamic Law and psychological standpoints.